Global Warming: Facing Confirmation Bias and Cognitive Dissonance with Hands-on Activities - Ã…Â lÃƒÂ©grovÃƒÂ¡, LeontÃƒÂ½na; Ã…Â lÃƒÂ©gr, Jan; StudniÃ„Âka, Filip (Universitas Terbuka, 2020)
Although global warming is an irrefutable scientific fact, many people, including those who often callÃ‚Â themselves skeptics and critical thinkers, are doubtful about this unambiguous fact. An extensiveÃ‚Â longitudinal survey amongst the students showed that even future teachers are not resistant to theseÃ‚Â misconceptions, even if they are presented with the conclusions of the scientific studies. In this paper, we show simpleÃ‚Â hands-onÃ‚Â classroom activities in which publicly available climate data are studied with methods previously known to students,Ã‚Â and simple atmospheric models are presented. These simple exercises can help future teachers to establish their own opinion on global warming based on the analysis of data and physical models and not on information from obscure websites and social networks.